## Non-alternating knots with 11 crossings

This table includes the knot designation, followed by the braid representation used by the braid programme, followed by the Alexander polynomial.

Output from braid v5.0.b1

```
-- 11(C1)
-s1s2s2s2-s3-s2-s2s1s2-s3s4s3-s2s3s2-s4
Alexander polynomial = -2t^4+4t^3-3t^2+4t-2

-- 11(C2)
s1s2s3-s4-s4-s4s3-s2-s1s4s5-s4-s3s2s3s4-s5-s4s3-s2s4-s3s5
Alexander polynomial = -2t^4+8t^3-13t^2+8t-2

-- 11(C3)
s1-s2s3s4-s3s2-s3-s2-s1-s4s3s2s3s3s3s2
Alexander polynomial = -2t^6+5t^5-3t^4+t^3-3t^2+5t-2

-- 11(C4)
-s1-s2-s3-s3-s2-s2s1-s4s3s2-s3s4-s3-s2-s4s3
Alexander polynomial = -2t^4+10t^3-15t^2+10t-2

-- 11(C5)
-s1s2s2s2-s3s2s1s2s2s2-s3-s2-s2
Alexander polynomial = t^6-2t^5+2t^4-3t^3+2t^2-2t+1

-- 11(C6)
s1s2-s3-s3-s3s2-s1s3s4s4s4-s3-s2s3-s2s4
Alexander polynomial = t^6-4t^5+8t^4-9t^3+8t^2-4t+1

-- 11(C7)
s1s2s3s3s3s2-s1-s2-s2-s2s3-s2s3
Alexander polynomial = t^8-3t^7+4t^6-5t^5+5t^4-5t^3+4t^2-3t+1

-- 11(C8)
-s1s2-s3s2-s1-s2-s2-s1-s3-s3-s3
Alexander polynomial = t^6-6t^5+12t^4-15t^3+12t^2-6t+1

-- 11(C9)
-s1-s2s3-s4s3s2s1s3s3s3s2-s3s4-s3-s2-s4-s3-s3
Alexander polynomial = -t^4+t^3+t^2+t-1

-- 11(C10)
s1-s2s3s4-s3s2-s3-s2-s1s2-s4-s5s4-s3-s3-s3s2s3s4-s3s5
Alexander polynomial = -t^4+5t^3-9t^2+5t-1

-- 11(C11)
s1s2s3s4s4s4s3-s2-s1-s3s2s3-s4s3-s2s4-s3s4
Alexander polynomial = -2t^6+6t^5-6t^4+5t^3-6t^2+6t-2

-- 11(C12)
-s1s2-s3s2s1-s4s3-s2-s3-s3-s2-s2-s4s3
Alexander polynomial = -3t^4+13t^3-19t^2+13t-3

-- 11(C13)
s1s2s3s3s3s2-s1-s2s3-s2s3s3s3
Alexander polynomial = t^8-3t^7+2t^6+t^5-3t^4+t^3+2t^2-3t+1

-- 11(C14)
-s1s2-s3s2s2s2-s1-s2-s2-s1-s3
Alexander polynomial = t^6-4t^5+6t^4-7t^3+6t^2-4t+1

-- 11(C15)
-s1s2-s3s2s1-s3-s3s2s2s2-s3-s2-s2
Alexander polynomial = t^6-4t^5+8t^4-11t^3+8t^2-4t+1

-- 11(C16)
s1-s2-s3s4-s3-s3-s3-s2-s2-s1s2s3s2s4
Alexander polynomial = t^6-6t^5+14t^4-17t^3+14t^2-6t+1

-- 11(C17)
s1s2s3s3s3s2-s1-s2-s2s3-s2s3s3
Alexander polynomial = -t^8+3t^7-4t^6+t^5+t^4+t^3-4t^2+3t-1

-- 11(C18)
-s1s2-s3s2s2-s1-s2-s2-s1-s3-s3
Alexander polynomial = -t^6+4t^5-10t^4+13t^3-10t^2+4t-1

-- 11(C19)
-s1s2s2-s3s2s1-s3s2s2s2-s3-s2-s2
Alexander polynomial = -t^6+4t^5-8t^4+9t^3-8t^2+4t-1

-- 11(C20)
s1-s2-s3s4-s3-s3-s2-s2-s1s2s3s2s4s4
Alexander polynomial = -t^6+6t^5-14t^4+19t^3-14t^2+6t-1

-- 11(C21)
s1s2-s3s2-s1s2s2s2s2s2-s3-s2-s2
Alexander polynomial = t^6-2t^5+t^3-2t+1

-- 11(C22)
s1s2-s3s2s1-s3s2s2s2s2s2
Alexander polynomial = t^8-3t^7+2t^6-t^5+t^4-t^3+2t^2-3t+1

-- 11(C23)
s1-s2-s3-s3-s3-s3s4-s3-s2-s1s3s4-s3s2s3s2
Alexander polynomial = t^6-4t^5+8t^4-9t^3+8t^2-4t+1

-- 11(C24)
s1-s2-s3-s3-s2-s2-s2-s2-s1-s2s3-s2s3
Alexander polynomial = t^6-6t^5+10t^4-11t^3+10t^2-6t+1

-- 11(C25)
s1s2-s3s2-s1s2-s4s3-s2s3s2s2s4-s3-s2-s2
Alexander polynomial = -2t^4+6t^3-7t^2+6t-2

-- 11(C26)
-s1s2-s3s2s1s3s3s4s3-s2s3-s2s4s3
Alexander polynomial = -2t^6+7t^5-7t^4+5t^3-7t^2+7t-2

-- 11(C27)
-s1s2-s3s4-s3-s2s1-s4-s4s3s2-s3-s3-s4s5s4s3-s2s3s4-s5
Alexander polynomial = -2t^4+8t^3-13t^2+8t-2

-- 11(C28)
s1-s2-s3-s3s4-s3s2-s3-s2-s2-s1-s2-s4s3-s2s3
Alexander polynomial = -2t^4+12t^3-19t^2+12t-2

-- 11(C29)
-s1s2-s3-s4s3s2s1-s3s5s4s3s2-s3-s3s4-s5-s4s3-s2-s3-s3
Alexander polynomial = -t^4+3t^3-5t^2+3t-1

-- 11(C30)
s1-s2s3-s2-s1s3s4-s3s2-s3-s2-s4-s3-s3-s2-s2
Alexander polynomial = -t^4+7t^3-11t^2+7t-1

-- 11(C31)
s1s2-s3s2-s1s2-s4s3s3-s2s3s2s4-s3-s2-s2
Alexander polynomial = -3t^4+11t^3-15t^2+11t-3

-- 11(C32)
-s1s2s2-s3s2s1s3s4s3-s2s3-s2s4s3
Alexander polynomial = -2t^6+8t^5-12t^4+13t^3-12t^2+8t-2

-- 11(C33)
-s1-s2-s3-s4s5s4s4s3s2s1-s4-s4s3-s4s5-s4-s3s2-s5s4s3-s4-s4-s5s4-s3-s2
Alexander polynomial = 2t^2-5t+2

-- 11(C34)
s1s2-s3s2-s1s3s4-s3s2-s3-s2-s4-s5-s4-s3s2-s3s4s3-s2s5
Alexander polynomial = 5t^2-11t+5

-- 11(C35)
s1s2-s3s2-s1s3s4s3-s2s3s2-s4-s5-s4s3-s2s3s4s3-s2s5
Alexander polynomial = 2t^4-13t^3+21t^2-13t+2

-- 11(C36)
-s1-s2s3-s4s3s2s1s3-s4-s3-s3-s3-s3s2-s3-s3-s4s3-s2s4
Alexander polynomial = -2t^4+7t^3-9t^2+7t-2

-- 11(C37)
-s1-s2-s3s4-s3s2s1s3s3s3-s4s3s2-s3s4-s3-s2-s4
Alexander polynomial = -2t^4+4t^3-3t^2+4t-2

-- 11(C38)
-s1-s2s3-s4s3s2s1s3s3s3-s4s3s2s3-s4s3-s2s4
Alexander polynomial = -t^6+7t^5-13t^4+15t^3-13t^2+7t-1

-- 11(C39)
-s1-s2-s3-s4s5-s4s3s2s1s4s3-s4s5-s4-s3s2-s5s4s3-s4-s4-s5s4-s3-s2
Alexander polynomial = t^4-t^3-t^2-t+1

-- 11(C40)
-s1-s2-s3-s4s5s4s4s3s2s1s4s3-s4s5-s4-s3s2-s5s4s3s4-s5s4-s3-s2
Alexander polynomial = 2t^4-10t^3+15t^2-10t+2

-- 11(C41)
s1-s2s3s4-s3-s3-s2s3s2-s4-s5-s4s3-s2-s1s3-s2s4s3-s2s5
Alexander polynomial = -2t^4+11t^3-19t^2+11t-2

-- 11(C42)
s1s2s3s3s3s2s2-s1-s2s3-s2s3s3
Alexander polynomial = t^8-3t^7+2t^6+2t^5-5t^4+2t^3+2t^2-3t+1

-- 11(C43)
-s1s2s2-s3s2s1s2s2s2-s3-s2-s2-s2
Alexander polynomial = -t^6+3t^5-6t^4+7t^3-6t^2+3t-1

-- 11(C44)
-s1s2-s3s2s2-s1-s2-s2-s2-s1-s3
Alexander polynomial = -t^6+5t^5-12t^4+15t^3-12t^2+5t-1

-- 11(C45)
s1s2s3s3s3s2s2-s1-s2-s2s3-s2s3
Alexander polynomial = -t^8+3t^7-4t^6+2t^5-t^4+2t^3-4t^2+3t-1

-- 11(C46)
-s1s2-s3s2s1-s3s2s2s2-s3-s2-s2-s2
Alexander polynomial = t^6-5t^5+10t^4-13t^3+10t^2-5t+1

-- 11(C47)
-s1s2-s3s2-s1-s2-s2-s2-s1-s3-s3
Alexander polynomial = t^6-7t^5+16t^4-21t^3+16t^2-7t+1

-- 11(C48)
s1-s2-s3s4-s3s2-s3-s2-s1-s4s3-s5s4-s3-s2s3s4s3s3-s2s5
Alexander polynomial = t^4-3t^2+1

-- 11(C49)
s1s2-s3s2-s1s2s2s2s2-s3-s2-s2-s2
Alexander polynomial = -t^6+3t^5-4t^4+3t^3-4t^2+3t-1

-- 11(C50)
s1s1s2s2s2s2s1s2-s3s2-s3
Alexander polynomial = t^8-3t^7+2t^6-t^4+2t^2-3t+1

-- 11(C51)
s1-s2s3-s2-s1s3s4-s3s2-s3-s2-s4-s3-s3-s3-s2
Alexander polynomial = -t^4+8t^3-13t^2+8t-1

-- 11(C52)
s1-s2-s3-s2-s2-s2-s1s3s4-s3-s2s3s4s3s3-s2
Alexander polynomial = -t^6+3t^5-6t^4+9t^3-6t^2+3t-1

-- 11(C53)
s1s2-s3s2-s1s2-s4s3-s2s3s2s4-s3-s2-s2-s2
Alexander polynomial = 3t^4-12t^3+19t^2-12t+3

-- 11(C54)
-s1s2-s3s2s1s3s4s3-s2s3-s2s4s4s3
Alexander polynomial = -2t^6+7t^5-8t^4+7t^3-8t^2+7t-2

-- 11(C55)
s1-s2-s3-s3-s3-s2-s2-s2-s1-s2s3-s2s3
Alexander polynomial = t^6-7t^5+14t^4-17t^3+14t^2-7t+1

-- 11(C56)
-s1-s2s3-s4s3s2s1s3s2-s3-s4s3-s2-s2-s2-s4-s3-s3-s3s4
Alexander polynomial = -2t^4+9t^3-13t^2+9t-2

-- 11(C57)
-s1s2s2-s3s2s1-s2s3-s2-s3-s4-s4s3-s4
Alexander polynomial = 2t^4-6t^3+9t^2-6t+2

-- 11(C58)
-s1-s2s3-s4s3s2s1s3s3-s4s3s2s3s3-s4s3-s2s4
Alexander polynomial = -t^6+7t^5-15t^4+19t^3-15t^2+7t-1

-- 11(C59)
-s1-s2-s2s3s2s2s2s1s2s2s2-s3s2s2s2
Alexander polynomial = t^8-3t^7+4t^6-4t^5+3t^4-4t^3+4t^2-3t+1

-- 11(C60)
s1-s2s3s3s3-s2-s2-s1s2s3s3s3s2
Alexander polynomial = -t^8+3t^7-6t^6+8t^5-9t^4+8t^3-6t^2+3t-1

-- 11(C61)
s1s2s2s2s1-s3-s3s2s2s2-s3
Alexander polynomial = -t^8+3t^7-6t^6+8t^5-9t^4+8t^3-6t^2+3t-1

-- 11(C62)
-s1-s2-s2s3s3s3-s2s1-s2-s3-s3-s2-s2
Alexander polynomial = -2t^6+7t^5-14t^4+17t^3-14t^2+7t-2

-- 11(C63)
-s1s2s2s2-s1-s3-s2-s2-s1-s3-s3
Alexander polynomial = -2t^6+7t^5-14t^4+17t^3-14t^2+7t-2

-- 11(C64)
s1s2-s3-s4-s4-s4-s3-s3-s2-s1-s3-s3-s2s3s4s3s2-s3
Alexander polynomial = -2t^6+9t^5-18t^4+23t^3-18t^2+9t-2

-- 11(C65)
s1s2s3s3s3s2s2-s1s2s3s3s3s2
Alexander polynomial = -t^8+t^7+2t^6-8t^5+11t^4-8t^3+2t^2+t-1

-- 11(C66)
-s1-s2-s2s3-s2-s2-s2s1s2s2s2-s3s2s2s2
Alexander polynomial = -t^4+2t^3-3t^2+2t-1

-- 11(C67)
-s1-s2-s2s3s3s3-s2s1s2-s3-s3s2s2
Alexander polynomial = -t^4+2t^3-3t^2+2t-1

-- 11(C68)
s1s2s2s3s3s3-s4s3-s2-s1-s2s3s4-s3-s3-s2
Alexander polynomial = t^6-6t^5+12t^4-13t^3+12t^2-6t+1

-- 11(C69)
s1s2-s3s4s5s4-s3-s3-s2-s1s3-s2-s3s4-s3s2-s5s4s3
Alexander polynomial = t^6-6t^5+16t^4-23t^3+16t^2-6t+1

-- 11(C70)
-s1s2-s3s2s1-s3s2s2s2-s3-s3-s2-s2
Alexander polynomial = t^6-5t^5+11t^4-15t^3+11t^2-5t+1

-- 11(C71)
s1s2-s3-s3-s3s2-s1s3s4-s3-s2s3s4-s3-s2s3-s2-s2
Alexander polynomial = t^6-7t^5+17t^4-21t^3+17t^2-7t+1

-- 11(C72)
s1s2s3-s4s3-s2-s1-s2s4-s3s4-s3s2s3s4s4s4s3
Alexander polynomial = -2t^6+7t^5-9t^4+9t^3-9t^2+7t-2

-- 11(C73)
-s1s2-s3s2s1-s4s3-s2-s4-s3-s3-s2-s2s3
Alexander polynomial = -4t^4+16t^3-23t^2+16t-4

-- 11(C74)
s1s1s1-s2-s1-s1s3-s2-s2-s2s3
Alexander polynomial = t^6-3t^5+5t^4-7t^3+5t^2-3t+1

-- 11(C75)
s1s2s3-s4-s4-s4s3-s2-s1-s4-s3-s3-s2s3s4s3s2-s3
Alexander polynomial = t^6-5t^5+11t^4-13t^3+11t^2-5t+1

-- 11(C76)
-s1s2s2-s3-s3s2s1s2s2s2-s3-s2-s2
Alexander polynomial = -t^6+3t^5-5t^4+5t^3-5t^2+3t-1

-- 11(C77)
s1-s2-s3-s3s4-s3-s2-s2-s1s2s3s2s4s4
Alexander polynomial = -t^6+5t^5-11t^4+15t^3-11t^2+5t-1

-- 11(C78)
s1s2s2s3s3s3-s4-s3-s2-s1-s2-s3s4s3s3-s2
Alexander polynomial = t^6-5t^5+13t^4-17t^3+13t^2-5t+1

-- 11(C79)
s1s2-s3-s4s5s4-s3-s3-s2-s1-s3-s2-s3s4-s3s2-s5-s4-s3
Alexander polynomial = t^6-6t^5+12t^4-15t^3+12t^2-6t+1

-- 11(C80)
-s1s2-s3s2s1-s3s2s2s2s3s3s2s2
Alexander polynomial = t^6-7t^5+15t^4-19t^3+15t^2-7t+1

-- 11(C81)
s1-s2-s3-s3-s3-s2-s1s3s4-s3-s2s3s4-s3-s2s3s2s2
Alexander polynomial = t^6-6t^5+16t^4-21t^3+16t^2-6t+1

-- 11(C82)
s1s2s3-s4s3-s2-s1-s2s4s3-s4s3s2-s3s4s4s4-s3
Alexander polynomial = -3t^4+10t^3-13t^2+10t-3

-- 11(C83)
-s1s2-s3s2s1s4-s3-s2s4s3s3-s2-s2s3
Alexander polynomial = 3t^4-8t^3+11t^2-8t+3

-- 11(C84)
s1s2-s3s4-s3-s2-s1-s2-s4-s3s4-s3s2-s3s4s4s4-s3
Alexander polynomial = -t^6+7t^5-16t^4+21t^3-16t^2+7t-1

-- 11(C85)
-s1-s2s3s3-s2-s2s1-s4s3-s2-s4s3-s2-s3
Alexander polynomial = t^6-7t^5+18t^4-23t^3+18t^2-7t+1

-- 11(C86)
s1s2s2-s3-s3-s3-s4s3-s2-s1-s2s3s4-s3-s3-s2
Alexander polynomial = -t^6+t^5+5t^4-9t^3+5t^2+t-1

-- 11(C87)
s1s2s3s4s5s4s3s3-s2-s1s3-s2-s3s4-s3s2-s5s4s3
Alexander polynomial = t^6-2t^5-2t^4+5t^3-2t^2-2t+1

-- 11(C88)
-s1s2-s3s2s1-s3-s2-s2-s2-s3-s3-s2-s2
Alexander polynomial = t^8-3t^7+t^6+4t^5-7t^4+4t^3+t^2-3t+1

-- 11(C89)
s1s2-s3s2-s1s3s4-s3-s2s3s4-s3-s2s3s3s3-s2-s2
Alexander polynomial = -t^6+3t^5-3t^4+3t^3-3t^2+3t-1

-- 11(C90)
s1s2s3-s4s3-s2-s1-s2s4-s3s4-s3s2s3-s4-s4-s4s3
Alexander polynomial = -2t^2+5t-2

-- 11(C91)
-s1s2-s3s2s1-s4s3s2-s4-s3-s3s2s2s3
Alexander polynomial = -2t^2+5t-2

-- 11(C92)
-s1-s1-s1-s2-s1-s1s3-s2-s2-s2s3
Alexander polynomial = t^8-3t^7+3t^6-2t^5+t^4-2t^3+3t^2-3t+1

-- 11(C93)
s1s2s3-s4-s4-s4s3-s2-s1-s4s3s3-s2s3s4s3s2s3
Alexander polynomial = -t^6+5t^5-9t^4+11t^3-9t^2+5t-1

-- 11(C94)
-s1s2s2-s3-s3s2s1-s2-s2-s2-s3-s2-s2
Alexander polynomial = -t^8+3t^7-5t^6+4t^5-3t^4+4t^3-5t^2+3t-1

-- 11(C95)
s1s2-s3-s3s4-s3s2s2-s1s2s3s2s4s4
Alexander polynomial = t^6-5t^5+13t^4-17t^3+13t^2-5t+1

-- 11(C96)
s1s2s2s2s1-s3s2-s3s2s2-s3
Alexander polynomial = -t^8+4t^7-8t^6+9t^5-9t^4+9t^3-8t^2+4t-1

-- 11(C97)
-s1-s2s3-s2s3s3-s2s1-s2-s3-s3-s2-s2
Alexander polynomial = -2t^6+8t^5-18t^4+23t^3-18t^2+8t-2

-- 11(C98)
-s1-s2-s3-s3-s3-s2s1s2-s3s2-s3-s3s2
Alexander polynomial = -t^8+4t^7-8t^6+9t^5-9t^4+9t^3-8t^2+4t-1

-- 11(C99)
s1-s2s3-s2-s2s1s3s2s2s1s3
Alexander polynomial = -2t^6+8t^5-18t^4+23t^3-18t^2+8t-2

-- 11(C100)
s1s2s3s3s3s2-s1-s2s3-s2s3-s2-s2
Alexander polynomial = t^8-4t^7+8t^6-13t^5+15t^4-13t^3+8t^2-4t+1

-- 11(C101)
-s1s2-s3s2-s1-s3-s3-s2-s2-s1-s3
Alexander polynomial = 2t^6-10t^5+20t^4-25t^3+20t^2-10t+2

-- 11(C102)
s1-s2s1-s2s1-s3-s2-s2-s2s1-s3
Alexander polynomial = t^8-4t^7+8t^6-13t^5+15t^4-13t^3+8t^2-4t+1

-- 11(C103)
-s1s2s2-s3s2-s3s2s1s2s2s3s3s2
Alexander polynomial = 2t^6-10t^5+20t^4-25t^3+20t^2-10t+2

-- 11(C104)
s1-s2-s2-s2s1-s3s2-s3s2s2-s3
Alexander polynomial = -1

-- 11(C105)
-s1-s2s3-s2s3s3-s2s1s2-s3-s3s2s2
Alexander polynomial = -2t^4+6t^3-9t^2+6t-2

-- 11(C106)
-s1-s2s3s3s3-s2s1s2-s3s2-s3-s3s2
Alexander polynomial = -1

-- 11(C107)
-s1-s2s3-s2-s2-s1s3s2s2-s1s3
Alexander polynomial = -2t^4+6t^3-9t^2+6t-2

-- 11(C108)
s1-s2s3s3s3-s2-s1-s2s3-s2s3-s2-s2
Alexander polynomial = -t^8+6t^7-16t^6+27t^5-33t^4+27t^3-16t^2+6t-1

-- 11(C109)
s1-s2s1-s2s1-s3s2s2s2s1-s3
Alexander polynomial = 2t^4-6t^3+7t^2-6t+2

-- 11(C110)
s1s2-s3s2s4-s3-s3s5s4s3s2-s1s2s3-s4s3-s5-s4s3s3s2
Alexander polynomial = t^4-9t^3+15t^2-9t+1

-- 11(C111)
s3-s4s3s2s1s3s2-s4-s3s5s4-s3-s2-s1s3-s2s3s4-s5
Alexander polynomial = -t^6+6t^5-14t^4+17t^3-14t^2+6t-1

-- 11(C112)
s2-s3s2-s5s4-s3s2s1-s2-s3-s4-s3s5s4s3-s2-s1s3-s4
Alexander polynomial = t^6-6t^5+18t^4-27t^3+18t^2-6t+1

-- 11(C113)
s2s3s2-s5s4s3s2s1-s2s3-s4s3s5s4s3-s2-s1s3-s4
Alexander polynomial = t^6-6t^5+10t^4-11t^3+10t^2-6t+1

-- 11(C114)
s1s2s3s4s5s4s3-s2-s1s3-s2-s3s4-s3s2-s5s4s3s4
Alexander polynomial = t^6-2t^5+t^3-2t+1

-- 11(C115)
-s1s2-s1s2s3-s2-s2s3-s2-s2s3
Alexander polynomial = -t^6+3t^5-3t^4+t^3-3t^2+3t-1

-- 11(C116)
s2-s1s2s2-s1-s1s3-s2s3-s2-s1
Alexander polynomial = t^6-4t^5+9t^4-13t^3+9t^2-4t+1

-- 11(C117)
-s2s3-s2s1s3s2s2-s3s2-s3s2s2-s1
Alexander polynomial = -t^6+6t^5-15t^4+19t^3-15t^2+6t-1

-- 11(C118)
-s2s3-s2s1s3-s2-s2-s3s2-s3-s2-s2-s1
Alexander polynomial = -t^6+5t^5-13t^4+17t^3-13t^2+5t-1

-- 11(C119)
s1s2s3s4-s5s4-s3-s2-s1s5s4s3s2s3-s4s3-s2s4s5-s4s3s4s4
Alexander polynomial = -6t^4+16t^3-21t^2+16t-6

-- 11(C120)
-s1s2s3-s4s3s3s2s1-s3-s4s3-s2-s3-s2-s5-s4-s3s2-s3s4s5
Alexander polynomial = -3t^4+13t^3-21t^2+13t-3

-- 11(C121)
s1s2s3s3s4-s3-s2-s1s3-s2s3s4-s5-s4-s3-s3s2s3-s4s3s5
Alexander polynomial = 3t^4-9t^3+11t^2-9t+3

-- 11(C122)
s1s2s3s3s4-s3-s2-s1s3s2s3s3s4-s5s4-s3-s2s3s4s3s5
Alexander polynomial = -5t^4+11t^3-13t^2+11t-5

-- 11(C123)
s3s2s1s2s3s3s3s4s3s3s2-s1s2-s3s2-s4
Alexander polynomial = 3t^6-6t^5+6t^4-5t^3+6t^2-6t+3

-- 11(C124)
-s3s2s4-s3s2s1-s2-s3-s4-s3s2s2s2s2-s1s2
Alexander polynomial = -t^6+t^5+3t^4-5t^3+3t^2+t-1

-- 11(C125)
s3s2s4s3s2s1-s2s3-s4s3s2s2s2s2-s1s2
Alexander polynomial = 3t^6-7t^5+11t^4-13t^3+11t^2-7t+3

-- 11(C126)
-s1-s1s2-s1s3-s2-s2s3-s2-s2s3
Alexander polynomial = -t^6+5t^5-13t^4+17t^3-13t^2+5t-1

-- 11(C127)
s2-s1s2s2-s1-s1s3s3-s2-s1s3
Alexander polynomial = t^6-4t^5+7t^4-9t^3+7t^2-4t+1

-- 11(C128)
-s2-s2s3-s2s1s2s2-s3s2-s3s2s2-s1
Alexander polynomial = -t^6+2t^5-t^4-t^3-t^2+2t-1

-- 11(C129)
-s2-s2s3-s2s1-s2-s2-s3s2-s3-s2-s2-s1
Alexander polynomial = t^6-7t^5+15t^4-19t^3+15t^2-7t+1

-- 11(C130)
-s1s2-s1-s3-s3-s2-s2-s2-s3s2-s3
Alexander polynomial = t^6-8t^5+17t^4-21t^3+17t^2-8t+1

-- 11(C131)
-s1-s2s3s2-s4-s3-s3-s2s3-s2s1-s2s3-s2s4s3
Alexander polynomial = -t^4+3t^2-1

-- 11(C132)
-s1s2-s3s2s1s2-s3-s3s2s4-s3s2s4s3
Alexander polynomial = t^6-6t^5+16t^4-21t^3+16t^2-6t+1

-- 11(C133)
s3-s2s1-s2-s2s4-s3s2-s1s4-s3-s3-s2s4
Alexander polynomial = 2t^4-6t^3+9t^2-6t+2

-- 11(C134)
-s2-s2-s2-s3s2-s3-s2-s2s1-s2s3-s2-s1
Alexander polynomial = t^6-7t^5+13t^4-15t^3+13t^2-7t+1

-- 11(C135)
s2s1s2s3s3s4-s3s2-s1s2s3s3s3s2-s4s3
Alexander polynomial = 3t^6-7t^5+9t^4-9t^3+9t^2-7t+3

-- 11(C136)
s3s2s4s3s2s1-s2s3s3-s4s3s2s2s2-s1s2
Alexander polynomial = 3t^6-8t^5+13t^4-15t^3+13t^2-8t+3

-- 11(C137)
-s2s3-s2s1s2-s3-s3-s4-s4-s3s2-s1-s3s4
Alexander polynomial = -3t^4+12t^3-17t^2+12t-3

-- 11(C138)
-s1s2-s3s2s1s2s3-s4s3s2-s3-s4s3-s4
Alexander polynomial = 3t^4-14t^3+23t^2-14t+3

-- 11(C139)
s1s2-s3s2-s1s3s4-s3-s3s2-s3s4-s3s2
Alexander polynomial = -t^6+7t^5-18t^4+25t^3-18t^2+7t-1

-- 11(C140)
s1s2-s3s4-s3s2-s1-s3-s2s3-s2s4s3s3
Alexander polynomial = t^4-8t^3+15t^2-8t+1

-- 11(C141)
-s1s2-s3s4s4s3-s4-s3-s2-s2-s3s1-s3s2-s3s4-s3-s2-s4s3
Alexander polynomial = -3t^4+16t^3-25t^2+16t-3

-- 11(C142)
s1-s2s1s2s3s3-s2-s1-s1-s1-s2-s3s2
Alexander polynomial = -t^6+t^5+3t^4-7t^3+3t^2+t-1

-- 11(C143)
s1s2s2s2-s3-s3s4s3-s2-s1s2s3-s4-s3s2-s3
Alexander polynomial = -t^6+2t^5-t^4+t^3-t^2+2t-1

-- 11(C144)
-s1s2-s3-s2-s2-s1-s2-s2-s2-s3s2
Alexander polynomial = t^6-4t^5+4t^4-3t^3+4t^2-4t+1

-- 11(C145)
s3-s2s1s3s2s3s3s4-s3s2-s1-s2s3s3s3-s4
Alexander polynomial = -t^6+5t^5-7t^4+7t^3-7t^2+5t-1

-- 11(C146)
s1-s2s3s4s3-s2-s1s3s3s2s3s3-s4s3-s2-s2
Alexander polynomial = t^6-5t^5+15t^4-21t^3+15t^2-5t+1

-- 11(C147)
-s1-s2-s2-s2s3s2s2-s1s2-s1-s1-s2-s3-s3s2
Alexander polynomial = t^6-5t^5+10t^4-13t^3+10t^2-5t+1

-- 11(C148)
s1-s2-s3-s3-s4-s3-s3-s3-s2-s1s3-s4-s3-s2s3-s2
Alexander polynomial = 3t^6-6t^5+4t^4-t^3+4t^2-6t+3

-- 11(C149)
s1s2s3-s4s3-s2-s1s4s3-s2s3-s2s4s3-s2s3
Alexander polynomial = 2t^6-9t^5+17t^4-19t^3+17t^2-9t+2

-- 11(C150)
s2-s1s2-s1s3s3s3s2-s1s2s3
Alexander polynomial = -t^8+4t^7-6t^6+4t^5-3t^4+4t^3-6t^2+4t-1

-- 11(C151)
-s1-s1s2-s1s3-s2s3-s2s3-s2s3
Alexander polynomial = t^6-6t^5+13t^4-17t^3+13t^2-6t+1

-- 11(C152)
-s1s2-s3s2s1s4-s3s2s4-s3s4-s3s2s3
Alexander polynomial = t^6-8t^5+22t^4-29t^3+22t^2-8t+1

-- 11(C153)
-s1s2-s3s2s1-s4s3s2s3-s4s3s2-s4s3
Alexander polynomial = 2t^6-8t^5+14t^4-15t^3+14t^2-8t+2

-- 11(C154)
-s1s2-s1s3-s2-s2s3-s2s3-s2s3
Alexander polynomial = t^6-5t^5+12t^4-17t^3+12t^2-5t+1

-- 11(C155)
-s1s2-s3s2-s1-s3-s2-s2-s2-s3s2
Alexander polynomial = -t^6+6t^5-17t^4+23t^3-17t^2+6t-1

-- 11(C156)
-s1s2-s1s3s2s2s2-s1s2s3s2
Alexander polynomial = -t^8+4t^7-7t^6+7t^5-7t^4+7t^3-7t^2+4t-1

-- 11(C157)
s2-s1s2-s1s3s3s2s2-s1s2s3
Alexander polynomial = -t^8+4t^7-7t^6+5t^5-3t^4+5t^3-7t^2+4t-1

-- 11(C158)
s2-s1s2-s1s3s3s2-s1-s1s2s3
Alexander polynomial = t^8-4t^7+7t^6-8t^5+7t^4-8t^3+7t^2-4t+1

-- 11(C159)
s1-s2s3-s2s1-s2-s3-s3-s3-s2s3
Alexander polynomial = -t^6+7t^5-19t^4+25t^3-19t^2+7t-1

-- 11(C161)
-s1s2s3-s4s3s2s1s3-s4s3s2-s3s4-s3-s2-s4
Alexander polynomial = 2t^6-8t^5+11t^4-9t^3+11t^2-8t+2

-- 11(C162)
s1s2-s3s2s1s2-s3s2-s3-s3-s3
Alexander polynomial = -t^8+4t^7-7t^6+10t^5-13t^4+10t^3-7t^2+4t-1

-- 11(C163)
s1s2-s3s4-s3-s3s2-s1-s2s3s4s4-s3-s2s3-s2
Alexander polynomial = -t^6+6t^5-16t^4+23t^3-16t^2+6t-1

-- 11(C164)
s1-s2s1-s3-s2s1-s2-s2-s3-s2-s2
Alexander polynomial = -t^8+4t^7-6t^6+2t^5+t^4+2t^3-6t^2+4t-1

-- 11(C165)
s1-s2s3-s2s4s3-s2-s1s2s3-s4s3s3-s2-s2s3
Alexander polynomial = -t^6+6t^5-15t^4+21t^3-15t^2+6t-1

-- 11(C166)
-s1-s2-s2-s3s2-s4-s3s2s1-s3s2-s3s4s3s3s2
Alexander polynomial = -t^6+7t^5-20t^4+29t^3-20t^2+7t-1

-- 11(C167)
s1s2-s3s4-s3-s3-s3s2-s1-s2s3s4-s3-s2s3-s2
Alexander polynomial = t^6-6t^5+16t^4-21t^3+16t^2-6t+1

-- 11(C168)
s1s2s2-s3s2s1s2-s3s2-s3-s3
Alexander polynomial = t^8-4t^7+8t^6-11t^5+11t^4-11t^3+8t^2-4t+1

-- 11(C169)
-s1s2-s3s2-s1-s3-s3-s2-s2-s3s2
Alexander polynomial = -t^6+6t^5-15t^4+19t^3-15t^2+6t-1

-- 11(C170)
-s1s2s2-s1s3s2s2-s1s2s3s2
Alexander polynomial = -t^8+4t^7-8t^6+7t^5-5t^4+7t^3-8t^2+4t-1

-- 11(C171)
-s1-s2-s2-s1-s3s2s2-s1s2-s3s2
Alexander polynomial = t^6-5t^5+11t^4-15t^3+11t^2-5t+1

-- 11(C172)
s1s2s2s3-s4s3s4-s3-s2-s1s2s2s3s4-s2s3
Alexander polynomial = -3t^4+14t^3-21t^2+14t-3

-- 11(C173)
-s1-s2s3s2s2-s1s2s4s3-s2s3s4s3s2
Alexander polynomial = -2t^6+9t^5-14t^4+15t^3-14t^2+9t-2

-- 11(C174)
-s1-s2-s2-s2-s1-s3s2-s1-s3s2-s3
Alexander polynomial = 2t^6-11t^5+24t^4-31t^3+24t^2-11t+2

-- 11(C175)
s2-s3s2s1-s3s2-s3s2s1s1-s3
Alexander polynomial = t^8-5t^7+10t^6-14t^5+15t^4-14t^3+10t^2-5t+1

-- 11(C176)
-s1-s1-s2-s2-s1-s3s2-s1-s3s2-s3
Alexander polynomial = 2t^6-11t^5+22t^4-27t^3+22t^2-11t+2

-- 11(C177)
-s1s2-s1s2s2-s1s3s2-s1s2s3
Alexander polynomial = t^8-5t^7+11t^6-16t^5+17t^4-16t^3+11t^2-5t+1

-- 11(C178)
-s1s2s2-s1-s3-s2-s2-s1-s3s2-s3
Alexander polynomial = -2t^6+9t^5-20t^4+25t^3-20t^2+9t-2

-- 11(C179)
-s1-s2-s2-s1-s3-s2-s2-s1-s3s2-s3
Alexander polynomial = -t^6-t^5+6t^4-9t^3+6t^2-t-1

-- 11(C180)
s1s2-s3s2s1-s3-s3s2-s3s2-s3
Alexander polynomial = -t^8+5t^7-11t^6+18t^5-23t^4+18t^3-11t^2+5t-1

-- 11(C181)
-s1-s2-s3s4s3-s2-s3s4-s3s4-s3-s2s1s2s3s2
Alexander polynomial = -t^6+7t^5-18t^4+25t^3-18t^2+7t-1

-- 11(C182)
-s1s2-s3s2-s1s2-s1-s3-s2-s2-s3
Alexander polynomial = -2t^6+9t^5-22t^4+29t^3-22t^2+9t-2

```